The military libraries classification of the Russian army - A. M. Panchenko (Библиосфера, 2015)
The second half of XIX - early XX centuries is a period of the most dynamic development of military libraries in Russia. This time is characterized by a variety of libraries of different types and forms with their inherent properties and distinctive features. Hence, different views and approaches to the problem of terminology, typology and classification of libraries appeared in papers of Russian librarianship researchers. There are no universal schemes in the historical-library studies. The proposed classification of military libraries is based on multiyear experience of studying the history of the military librarianship. It was collected and analyzed about 300 systematic (mainly) and alphabetical book catalogs (and amendments thereto) in military libraries, published in 1862-1916, as well as more than 70 book catalogs of libraries in military schools (1830-1916). Studied sources give an opportunity to structure the different types and forms of military libraries not only in a chronological order, but according to type-forming functions: military research, military educational, army officers, special, soldiers, as well as book collections of famous military leaders. To characterize some groups of the military libraries more complete their different hierarchical scheme are used.